Percepção de docentes brasileiros sobre as relações entre saúde, religião, espiritualidade e seu ensino - Silva, Taís Oliveira da (Horizonte, 2021)
Despite the greater recognition of the importance of the relationships between health, religion and spirituality in health care, Brazilian universities still do not provide adequate training in this area. The aim of this article is to understand how professors at a Brazilian public university perceive the relationships between health, religion, spirituality and their teaching. 10 teachers were submitted to a semi-structured interview and the data were analyzed through content analysis. Three thematic nuclei were found and, from these, five categories emerged: Religion and Spirituality: Overlapping concepts?; Good or bad for health?; Dimension excluded from clinical practice; Teaching: It would be nice, but not now; Questions and barriers to inclusion in teaching. The results showed that the participants overlapped the concepts of religion and spirituality, recognized their positive impacts on health, however, they emphasized their problematic aspects. The teaching of health, religion and spirituality was not considered a priority and the beliefs of the faculty seem to influence this position. Given the quantity and quality of scientific evidence on the positive impact of religion/spirituality on health, the inclusion of this topic in the training of health professionals should not only depend on the perceptions and/or preferences of the university faculty.